Nested Case–Control Study of Selected Systemic Autoimmune Diseases in World Trade Center Rescue/Recovery Workers. Issue 5 (May 2015) - Webber, M. P.; Moir, W.; Zeig‐Owens, R.; Glaser, M. S.; Jaber, N.; Hall, C.; Berman, J.; Qayyum, B.; Loupasakis, K.; Kelly, K.; Prezant, D. J.
<x xml:space="preserve">Abstract</x> Objective To test the a priori hypothesis that acute and chronic work exposures to the World Trade Center (WTC) site on or after September 11, 2001 were associated with risk of new‐onset systemic autoimmune diseases. Methods A nested case–control study was performed in WTC rescue/recovery workers who had received a rheumatologist‐confirmed systemic autoimmune disease diagnosis between September 12, 2001 and September 11, 2013 (n = 59), each of whom was individually matched to 4 randomly selected controls (n = 236) on the basis of year of hire (±1 year), sex, race, and work assignment (firefighter or emergency medical service). Acute exposure was defined according to the earliest time of arrival (morning of 9/11 versus later) at the WTC site, and chronic exposure was defined as duration (number of months) of WTC site–related work. Rheumatologists were blinded with regard to each subject's exposure status. The conditional odds ratios (CORs) with 95% confidence intervals (95% CIs) for incident autoimmune disease were derived from exact conditional logistic regression models. Results Rheumatoid arthritis was the most common autoimmune diagnosis (37% of subjects), followed by spondyloarthritis (22%), inflammatory myositis (14%), systemic lupus erythematosus (12%), systemic sclerosis (5%), Sjögren's syndrome (5%), antiphospholipid syndrome (3%), and granulomatosis with polyangiitis (Wegener's) (2%). The COR for incident autoimmune disease increased by 13% (COR 1.13, 95% CI 1.02–1.26) for each additional month worked at the WTC site. These odds were independent of the association between high acute exposure (working during the morning of 9/11) and disease outcome, which conveyed an elevated, but not statistically significant, risk (COR 1.85, 95% CI 0.86–3.89). Conclusion Prolonged work at the WTC site, independent of acute exposure, was an important predictor of post‐9/11 systemic autoimmune diseases. The WTC Health Program should expand surveillance efforts for those with extended exposures, as early detection can facilitate early treatment, which has been shown to minimize organ damage and improve quality of life.